2010
DOI: 10.5229/jkes.2010.13.1.057
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Electrochemical Synthesis of Highly Conductive and Processable PolyProDOP-alkyl Derivatives

Abstract: : New monomers, possessing various alkyl substituents on propylene dioxypyrrole, were synthesized. The monomers could be easily polymerized to produce highly conductive and soluble polymers. The corresponding polymers showed excellent solubility, retaining electrochemical and optical properties of their parent polymer [poly(propylene dioxypyrrole)]. The conductivities of chemically prepared polymers were quite high in a range of 20 and 60 Scm −1. Solubility of the polymer in a common organic solvent was as hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The fluorinated isocyanate was synthesized from a fluorinated acid chloride in the presence of trimethylsilyl azide . 2‐(2,3‐Dihydro‐[1,4]dioxino[2,3‐ c ]pyrrol‐6‐yl)ethanol (EDOP‐OH) was synthesized in ten steps from iminodiacetic acid using a procedure reported in the literature (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorinated isocyanate was synthesized from a fluorinated acid chloride in the presence of trimethylsilyl azide . 2‐(2,3‐Dihydro‐[1,4]dioxino[2,3‐ c ]pyrrol‐6‐yl)ethanol (EDOP‐OH) was synthesized in ten steps from iminodiacetic acid using a procedure reported in the literature (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
“…For instance, some derivatives of 3,4‐alkylenedioxypyrrole, such as, 3,4‐ethylenedioxypyrrole (EDOP), exhibit an exceptional polymerization capacity with one of the lowest oxidation potentials. Moreover, the resulting conducting polymers may also display unique optoelectronic properties . However, owing to the difficulty of synthesizing such derivatives (usually in more than eight steps), they have been only moderately studied in the literature so far.…”
Section: Introductionmentioning
confidence: 99%
“…The surface structures are highly dependent on electrochemical parameters and also on the monomer structure. It was shown that 3,4-ethylenedioxypyrrole (EDOP) and 3,4-propylenedioxypyrrole (ProDOP) derivatives have unique properties in term of polymerization capacity but also in terms of their optoelectronic and wetting properties. Indeed, in comparison with classical pyrrole derivatives, the presence of two alkoxy groups in the 3 and 4 positions has several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Among the monomers usable for the electropolymerization, that of the 3,4-ethylenedioxypyrrole (EDOP) family offers exceptional polymerization capacity and lead to conducting polymers with unique optoelectronic properties. However, due to the extreme difficulty to synthesize these monomers, usually obtained in about 10 steps, the study of these derivatives remains a challenge. Previously, superoleophobic properties and superhydrophobic properties were obtained using fluorinated , and hydrocarbon chains, respectively. These exceptional properties were in part due to the presence of nanoporosity, which induces a high increase in the contact angles.…”
Section: Introductionmentioning
confidence: 99%